2018
DOI: 10.1016/j.celrep.2018.01.078
|View full text |Cite
|
Sign up to set email alerts
|

Dissonant Representations of Visual Space in Prefrontal Cortex during Eye Movements

Abstract: SUMMARY We used local field potentials (LFPs) and spikes to investigate representations of visual space in prefrontal cortex and the dynamics of those representations during eye movements. Spatial information contained in LFPs of the frontal eye field (FEF) was differentially distributed across frequencies, with a majority of that information being carried in alpha and high-gamma bands and minimal signal in the low-gamma band. During fixation, spatial information from alpha and high-gamma bands and spiking act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 88 publications
0
16
2
Order By: Relevance
“…These dynamics have yet to be demonstrated in PFC but their properties in other areas argue against a role. RF contraction effects extend to only ~300 ms after a saccade in area V4 (Neupane et al, 2016) and the frontal eye field (Chen et al, 2018), whereas poor cross-decoding extends to over 500 ms in our results. Contraction effects in V4 occur mainly for neurons with RF in the same hemifield as the saccade endpoint (Neupane et al, 2016), whereas in the key ipsilateral-to-contralateral condition in our results, RFs would be in the opposite hemifield to the saccade.…”
Section: Discussioncontrasting
confidence: 59%
“…These dynamics have yet to be demonstrated in PFC but their properties in other areas argue against a role. RF contraction effects extend to only ~300 ms after a saccade in area V4 (Neupane et al, 2016) and the frontal eye field (Chen et al, 2018), whereas poor cross-decoding extends to over 500 ms in our results. Contraction effects in V4 occur mainly for neurons with RF in the same hemifield as the saccade endpoint (Neupane et al, 2016), whereas in the key ipsilateral-to-contralateral condition in our results, RFs would be in the opposite hemifield to the saccade.…”
Section: Discussioncontrasting
confidence: 59%
“…In these models, connections between visual neurons with receptive fields spatially separated by the saccade vector can be used to predict post-saccadic visual stimulus location and compensate for retinal image shifts during the saccade (Neupane et al, 2017; Quaia et al, 1998; Wang et al, 2016). However, forward remapping models have been challenged by Zirnsak and colleagues (Chen et al, 2018; Zirnsak et al, 2014), whose results suggested that the early findings were affected by the low spatial resolution of the receptive field mapping technique (Duhamel et al, 1992; Sommer and Wurtz, 2006; Walker et al, 1995). More detailed FEF receptive field mapping suggested that, before a saccade, cells preferentially respond to stimuli presented near the saccade target rather than at the remapped target location.…”
Section: Discussionmentioning
confidence: 99%
“…Remapping can facilitate tracking of task-relevant objects across saccades and allow rapid comparison between pre- and post-saccadic visual inputs (Crapse and Sommer, 2012). However, this remapping hypothesis has been challenged with new data collected within the FEF (Chen et al, 2018; Zirnsak and Moore, 2014). These studies found that, before a saccade, neurons respond to stimuli presented near the saccade target rather than to stimuli presented at remapped locations of the recorded receptive field (RF).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies generated CSD data in FEF (47) and LIP (48) using visual stimulation (FEF: 1 degree of visual angle square at 60% contrast; LIP: diffuse light). Our CSD profiles generated with auditory stimulation were roughly consistent with these previous studies of FEF and LIP in so far as sensory stimulation elicited early sinks in middle layers (which would be predicted based on auditory stimulation activating middle cortical layers relatively early).…”
Section: Current Source Density (Csd)mentioning
confidence: 99%